4CPS-108 A review of infliximab biosimilar to biosimilar switch: Remsima to Flixabi. (24th March 2020) - O'neill, R; Singh, S; Luber, R
Abstract : Background and importance: In 2016, the local commissioning group and the gastroenterology directorate at a large acute teaching hospital switched all patients with inflammatory bowel disease (IBD) from the infliximab originator Remicade to the biosimilar Remsima. The success of this switch along with the emergence of more infliximab biosimilars with a license was an incentive for a biosimilar to biosimilar switch to be considered. Aim and objectives: The aim of this work was to assess the impact of a biosimilar to biosimilar switch in a large IBD unit. All IBD patients to switch from biosimilar Remsima to biosimilar Flixabi by August 2019. To obtain feedback from patients on the switch process using a patient survey. To assess the safety of the switch and to record if any adverse effects were experienced. Material and methods: A letter explaining the switch along with a frequently asked question document was sent to each patient prescribed Remsima for the treatment of IBD. Data were collected for each patient included: current infliximab dose (mg/kg), frequency of infusions (Q), patient weight (kg), calculated dose (mg), number of 100 mg vials per dose, cost per dose per patient for Remsima and Flixabi, predicted saving and whether this was the patients first or second switch. Results: All IBD patients (100%, n=227) switched from biosimilar Remsima to biosimilar Flixabi. To date, 5.4% (n=2) of patients have reported adverse events through the survey. A total of 86% (n=32) of patients would still like to be informed in writing about similar switches in the future. Conclusion and relevance: The objective to switch IBD patients to Flixabi was achieved ahead of time and without any resistance from patients. Overall, the switch was well received, patients were satisfied with the process and 99.2% of patients did not report any adverse events. The two reports of adverse effects were attributable to changes in the rate of administration rather than the drug. This study is ongoing and aims to address the concerns of multiple switches on immunogenicity and drug resistance by checking trough drug levels, antibodies, disease scores and C reactive protein pre and post switch. The data collected to date anecdotally showed that there was no negative clinical impact of multiple switches. References and/or acknowledgements: No conflict of interest.